Injection molding and shear‐induced stress simulation of poly (styrene‐ethylene‐butylene‐styrene) and polypropylene blends. Issue 19 (4th January 2022) - Chen, Yaowei; Yang, Jian; He, Wenjun; Liu, Lilan; Niu, Xinsheng; Li, Chao; Xiong, Mengyuan; Li, Xiaoyan
Abstract: In this article, the structure and rheological properties of poly (styrene‐ethylene‐butylene‐styrene) (SEBS) triblock copolymer blends are analyzed. The influence of polypropylene content on the three SEBS blends was discussed, the viscoelastic response and phase structure evolution during injection molding were studied. According to the capillary flow test data, the least square method is used to fit the viscosity parameters of the cross‐WLF model. The filling length of the spline was tested by adjusting the injection molding process parameters, and its accuracy was verified by comparing the filling simulation with the experimental results. Numerical simulation is used to predict the shear rate distribution of injection‐molded samples, and the shear sensitivity and residual stress of SEBS blends with different phase structures are analyzed. Based on the phase structure analysis and rheological properties, this article predicts the filling properties of triblock copolymer composites, which can be used to construct the flow‐induced structure–property relationship of complex polymer blends. Abstract :